High-Flow Nasal Oxygen Improves Safe Apnea Time in Morbidly Obese Patients Undergoing General Anesthesia: A Randomized Controlled Trial. (October 2019) - Wong, David T.; Dallaire, Amelie; Singh, Kawal Preet; Madhusudan, Poorna; Jackson, Timothy; Singh, Mandeep; Wong, Jean; Chung, Frances
Abstract : BACKGROUND: Morbidly obese patients undergoing general anesthesia are at risk of hypoxemia during anesthesia induction. High-flow nasal oxygenation use during anesthesia induction prolongs safe apnea time in nonobese surgical patients. The primary objective of our study was to compare safe apnea time, between patients given high-flow nasal oxygenation or conventional facemask oxygenation during anesthesia induction, in morbidly obese surgical patients. METHODS: Research ethics board approval was obtained. Elective surgical patients ≥18 years with body mass index ≥40 kg·m −2 were included. Patients with severe comorbidity, gastric reflux disease, known difficult airway, or nasal obstruction were excluded. After obtaining informed consent patients were randomized. In the intervention (high-flow nasal oxygenation) group, preoxygenation was provided by 100% nasal oxygen for 3 minutes at 40 L·minute −1 ; in the control group, preoxygenation was delivered using a facemask with 100% oxygen, targeting end-tidal O2 >85%. Anesthesia was induced with propofol, remifentanil, and rocuronium. Bag-mask ventilation was not performed. At 2 minutes after rocuronium, videolaryngoscopy was performed. If the laryngoscopy grade was I or II, laryngoscope was left in place and the study was continued; if grade III or IV was observed, the patient was excluded from the study. During the apnea period, high-flow nasal oxygenation patients received nasal oxygen at 60 L·minute −1 ; control group patients received no supplemental oxygen. The primary outcome, safe apnea time, was reached when oxygen saturation measured by pulse oximetry (SpO2 ) fell to 95% or maximum 6 minutes of apnea. The patient was then intubated. T tests and χ 2 analyses were used to compare groups. P < .05 was considered significant. RESULTS: Forty patients completed the study. Baseline parameters were comparable between groups. Safe apnea time was significantly longer (261.4 ± 77.7 vs 185.5 ± 52.9 seconds; mean difference [95% CI], 75.9 [33.3–118.5]; P = .001) and the minimum peri-intubation SpO2 was higher (91.0 ± 3.5 vs 88.0 ± 4.8; mean difference [95% CI], 3.1 [0.4–5.7]; P = .026) in the high-flow nasal oxygenation group compared to the control group. CONCLUSIONS: High-flow nasal oxygenation, compared to conventional oxygenation, provided a longer safe apnea time by 76 seconds (40%) and higher minimum SpO2 in morbidly obese patients during anesthesia induction. High-flow oxygenation use should be considered in morbidly obese surgical patients.